Long‐term plasma exchange in pediatric CIDP. Issue 6 (7th February 2015) - Lucchetta, Marta; Vidal, Enrico; Sartori, Stefano; Campagnolo, Marta; Torre, Chiara Dalla; Marson, Piero; Manara, Renzo; Briani, Chiara
Abstract : Therapeutic plasma exchange (TPE) is not frequently used in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) because it usually gives only a short‐term benefit. We report on a 16‐year‐old boy with renal insufficiency undergoing hemodialysis who developed CIDP and underwent TPE with dramatic long‐term response to therapy. Nerve ultrasound and MRI findings are also reported. In our patient TPE was chosen because he was already undergoing hemodialysis. Though it is not considered a first‐line therapy in pediatric CIDP, TPE may be a good therapeutic choice also in long‐term period. J. Clin. Apheresis 30:364–366, 2015. © 2015 Wiley Periodicals, Inc.